Mandibular Symphysis Morphology and Dimensions in Different Anteroposterior Jaw Relationship in the Himachali Population - Disha Sharma; Gaurav Thakur; Deepak Gurung; Amrita Thakur (Dentistry and Medical Research)
Introduction: The aim and objectives of this study were to assess the morphology and dimensions of the mandibular symphysis (MS) in different antero-posterior (AP) skeletal jaw relationships and to assess if the alveolar part of MS compensates for the skeletal relationship in the Himachali population. Materials and Methods: The study sample consisted of pretreatment lateral cephalograms of 90 subjects (mean age 12 ± 4) who were referred to the department for orthodontic treatment. The study subjects were of Himachali ethnic origin, residents of Himachal Pradesh from the last three generations. The subjects were divided into three groups of 30 each according to their skeletal AP jaw relationship (Class I, Class II, or Class III relationship). Class I skeletal relationship was considered when A point, nasion, B point (ANB) angle 3 ± 1, Class II skeletal relationship was considered when ANB angle was >4, and Class III skeletal relationship was considered when ANB angle was <2°. Results: In linear measurements Id-B and Pog-Me showed highest value for Class III subjects, but the differences were statistically nonsignificant. In angular measurements, Class III subjects showed larger B-B1-Gn angle (vertical dimension of MS) than Class I and Class II subjects and the differences between three groups were statistically significant. The inclination of the alveolar part was significantly larger in Class III shown by a small Id-B/Md angle. Inclination of the skeletal part showed statistically nonsignificant difference between the three groups. Conclusions: The Class III skeletal jaw relationship exhibited an increase in the vertical dimension, a less concavity of anterior contour of symphysis, more inclination of the alveolar part toward the mandibular plane than other sagittal relationships suggesting compensation for the skeletal pattern of the jaws.